Sub‐50 nm Iron–Nitrogen‐Doped Hollow Carbon Sphere‐Encapsulated Iron Carbide Nanoparticles as Efficient Oxygen Reduction Catalysts. Issue 7 (12th May 2018) - Tan, Haibo; Li, Yunqi; Kim, Jeonghun; Takei, Toshiaki; Wang, Zhongli; Xu, Xingtao; Wang, Jie; Bando, Yoshio; Kang, Yong‐Mook; Tang, Jing; Yamauchi, Yusuke
Abstract: Sub‐50 nm iron–nitrogen‐doped hollow carbon sphere‐encapsulated iron carbide nanoparticles (Fe3 C‐Fe, N/C) are synthesized by using a triblock copolymer of poly(styrene‐ b ‐2‐vinylpyridine‐ b ‐ethylene oxide) as a soft template. Their typical features, including a large surface area (879.5 m 2 g −1 ), small hollow size (≈16 nm), and nitrogen‐doped mesoporous carbon shell, and encapsulated Fe3 C nanoparticles generate a highly active oxygen reduction reaction (ORR) performance. Fe3 C‐Fe, N/C hollow spheres exhibit an ORR performance comparable to that of commercially available 20 wt% Pt/C in alkaline electrolyte, with a similar half‐wave potential, an electron transfer number close to 4, and lower H2 O2 yield of less than 5%. It also shows noticeable ORR catalytic activity under acidic conditions, with a high half‐wave potential of 0.714 V, which is only 59 mV lower than that of 20 wt% Pt/C. Moreover, Fe3 C‐Fe, N/C has remarkable long‐term durability and tolerance to methanol poisoning, exceeding Pt/C regardless of the electrolyte. Abstract : Sub‐50 nm iron–nitrogen‐doped hollow carbon sphere‐encapsulated iron carbide nanoparticles (Fe3 C‐Fe, N/C) are synthesized by using a triblock copolymer of poly(styrene‐ b ‐2‐vinylpyridine‐ b ‐ethylene oxide) as a soft template. Their typical features include a large surface area (879.5 m 2 g −1 ), small hollow size (≈16 nm), and nitrogen‐doped mesoporous carbon shell. Encapsulated Fe3 C nanoparticles generate a highly active oxygen reduction reaction performance.